2007
DOI: 10.1007/s00204-007-0184-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the anticancer dehydrotarplatin on cytochrome P450 and antioxidant enzymes in male rat tissues

Abstract: The effect of dehydrotarplatin (DTP), a new antineoplastic drug analogous to cisplatin, and its metabolite (Triacid) on the hepatic, renal and testicular CYP and antioxidant enzymes of male rats was investigated. The rats were treated i.p. with a single dose of DTP (25 mg kg(-1) day(-1)) or Triacid (17.5 mg kg(-1) day(-1)) and analysed 3 or 7 days post treatment. Three days after treatment, both drugs reduced body and liver weights, which partially recovered the control level after 7 days. DTP and, to a less e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The significant reduction in GSH levels promoted by CP represents an alteration in the cellular redox state, suggesting that the cells could be more sensitive to ROS. This leads to a reduction in effectiveness of the antioxidant enzyme defense system [28]. In this study, GSH levels in the kidney tissues of rats treated with CP were lower (28%) than the control groups (p<0.05).…”
Section: Discussionmentioning
confidence: 48%
“…The significant reduction in GSH levels promoted by CP represents an alteration in the cellular redox state, suggesting that the cells could be more sensitive to ROS. This leads to a reduction in effectiveness of the antioxidant enzyme defense system [28]. In this study, GSH levels in the kidney tissues of rats treated with CP were lower (28%) than the control groups (p<0.05).…”
Section: Discussionmentioning
confidence: 48%
“…The significant reduction in GSH levels promoted by CDDP represents an alteration in the cellular redox state, suggesting that the cells could be more sensitive to ROS. This leads to a reduction in effectiveness of the antioxidant enzyme defense system [40]. In this study, GSH levels in the liver and kidney tissues of rats treated with CDDP were lower than the control group's.…”
Section: Discussionmentioning
confidence: 49%
“…The therapeutic strategy to prevent the renal toxicity is to decrease the production of ROS as much as possible or neutralize them as early as possible. The present results clarified that pretreatment with ozone significantly prevented CPinduced lipid peroxidation which manifested in reduced (MDA) and increased tGSH in the renal tissue which could be explained by decreasing the ROS formation through improvement in oxidant status [48,49] . Our data confirmed that ozone pretreatment significantly reduced urea and creatinine, improved renal function and demonstrated increase in SOD activity and hence, morphology and histological appearance.…”
Section: Table (1): Effect Of Ozone On Serum and Kidney Biochemical Psupporting
confidence: 58%